Polyhydroxyalkanoates: Naturally occurring microbial polymers suitable for nanotechnology applications - De Paula-Elias, Fabrício C.; De Paula, Carolina B. C. [UNESP]; De Oliveira, Nayra M. L.; De Almeida, Alex F.; Contiero, Jonas [UNESP] (Elsevier, 2021)
Polyhydroxyalkanoates (PHAs) are intracellular microbial polyesters synthesized by many species of Bacteria and Archaea, generally under nutrient limitation and excess of carbon source as storage granules of energy and also conferring stress resistance to prokaryotes. PHAs are naturally occurring, and the choice of microbial strains and carbon sources for cell cultivations results in biopolymers with different physicochemical properties. Cupriavidus necator is a bacterial strain able to synthesize a high crystalline polymer, poly(3-hydroxybutyrate), the most common of all PHAs; whereas Pseudomonas species produce PHAs with medium chain-length monomers, which exhibit elastomeric properties as natural rubbers. This variety of monomer composition associated with high biocompatibility and biodegradability makes PHAs also feasible for compostable applications and meet the standard specification for marine degradability. Due to their high versatility as natural chemicals and their ecologically friendly properties, PHAs have drawn attention for a wide range of applications from which the PHA nanocomposites have become a promising alternative to petrochemical polymers for nanoscale applications, especially those involved in biomedical materials. This review chapter introduces PHAs from their microbial synthesis, polymer structure to recent applications, with special focus on nanoscience applications. PHA as scaffolds for tissue engineering, nanofibers and particles for catalyst immobilization and drug delivery systems are topics addressed in this chapter. Finally, the future prospects and economical challenges to be overcome by the PHA industry are discussed in this review chapter from a green chemistry background.
Keywords: Bioplastics; Drug delivery system; Enzyme immobilization; Nanotechnology; Polyhydroxyalkanoate; Tissue engineering